Biomedical Imaging Technologies for Cardiovascular Disease - Garcia Flores, Julio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to provide an update on the biomedical imaging technologies that can be used for cardiovascular diseases, including Doppler echocardiography, magnetic resonance imaging and positron emission tomography. Cardiovascular disease imaging assessment includes anatomy, hemodynamics, and tissue biomarkers, which aid the stratification of patient risk and therapy. In addition, this Special Issue includes articles that discuss the recent integration of artificial intelligence and machine learning, in order to support novel approaches to personalized image-based diagnosis.